2016
DOI: 10.2119/molmed.2015.00255
|View full text |Cite
|
Sign up to set email alerts
|

Combined Administration of Human Ghrelin and Human Growth Hormone Attenuates Organ Injury and Improves Survival in Aged Septic Rats

Abstract: Sepsis is a major healthcare concern, especially in the elderly population. The use of an animal model closely resembling clinical conditions in this population may provide a better prediction in translating bench studies to the bedside. Ghrelin inhibits sympathetic nerve activity and inflammation in young septic animals; however, aged animals become hyporesponsive to ghrelin. In this study, we evaluated the efficacy of combined human ghrelin and growth hormone (GH) for sepsis treatment in the elderly utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 59 publications
2
40
0
1
Order By: Relevance
“…Likewise, immune cells in septic patients have also been reported to suffer from anergy and therefore fail to proliferate or secrete cytokines in response to their specific antigens [3, 39]. Furthermore, defective T cell proliferation and cytokine secretion were shown to be correlated with higher mortality in septic patients [40], which corresponds to our previous survival study in septic aged rats [22]. …”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Likewise, immune cells in septic patients have also been reported to suffer from anergy and therefore fail to proliferate or secrete cytokines in response to their specific antigens [3, 39]. Furthermore, defective T cell proliferation and cytokine secretion were shown to be correlated with higher mortality in septic patients [40], which corresponds to our previous survival study in septic aged rats [22]. …”
Section: Discussionsupporting
confidence: 66%
“…Using the clinically-relevant CLP model of polymicrobial sepsis [33]. we have previously reported that combined treatment with human Ghr and GH improves 10-day survival in septic aged rats from 29% to 64% [22]. In this study, we further demonstrated that combined treatment with human Ghr and GH restores the responsiveness of isolated splenocytes to LPS- and anti-CD3/anti-CD28 antibody-stimulation; prevents the loss of splenic CD4 + and CD8 + T cells by apoptosis; reduces the splenic T reg population; inhibits the expression of splenic PD-1; and increases the expression of splenic HLA-DR in septic aged rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations